45+x=(13+x)+(4+x)+(10+x)

Simple and best practice solution for 45+x=(13+x)+(4+x)+(10+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 45+x=(13+x)+(4+x)+(10+x) equation:


Simplifying
45 + x = (13 + x) + (4 + x) + (10 + x)

Remove parenthesis around (13 + x)
45 + x = 13 + x + (4 + x) + (10 + x)

Remove parenthesis around (4 + x)
45 + x = 13 + x + 4 + x + (10 + x)

Remove parenthesis around (10 + x)
45 + x = 13 + x + 4 + x + 10 + x

Reorder the terms:
45 + x = 13 + 4 + 10 + x + x + x

Combine like terms: 13 + 4 = 17
45 + x = 17 + 10 + x + x + x

Combine like terms: 17 + 10 = 27
45 + x = 27 + x + x + x

Combine like terms: x + x = 2x
45 + x = 27 + 2x + x

Combine like terms: 2x + x = 3x
45 + x = 27 + 3x

Solving
45 + x = 27 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
45 + x + -3x = 27 + 3x + -3x

Combine like terms: x + -3x = -2x
45 + -2x = 27 + 3x + -3x

Combine like terms: 3x + -3x = 0
45 + -2x = 27 + 0
45 + -2x = 27

Add '-45' to each side of the equation.
45 + -45 + -2x = 27 + -45

Combine like terms: 45 + -45 = 0
0 + -2x = 27 + -45
-2x = 27 + -45

Combine like terms: 27 + -45 = -18
-2x = -18

Divide each side by '-2'.
x = 9

Simplifying
x = 9

See similar equations:

| 5+12-1=0 | | 2x^2-8x+23=0 | | log^8(3x-9)=2 | | 2(x-12)=3(x+15) | | 4c-8=7c+7 | | 4.5+8.5(1-4k)=-25.5 | | 2r-7=6+r | | 12a-4+3(a-11)=23 | | 2-3x=5+8x | | -8x-3+7+2x=5 | | 12x=16(x-1) | | 5(7x-6)=390 | | 9x+3x-10-3=(3x+x) | | -20.5=3.5f+8.5f | | 0.5(60+2y)-y=-30 | | 10-r-21r^2=o | | 8x-2x+10=24 | | 5Z-25= | | 26-6n=8+2(-4+2) | | -10w+6w= | | 0.5x-y=30 | | 7(d-2)=5d+2 | | x+(x+10)5=550 | | 21=9x+10 | | 6x+y=110 | | 4x+18-3x=-5-13 | | 5*w*6=126 | | 0.5-0.5(2x+3)=-0.6(x+4) | | 24-2x=10+5x | | 3x+2(4x-6)=4-x | | 26.5=-5+9.5(x+5.5) | | 3(1+y)-3y=3 |

Equations solver categories